EURYPEGASUS DRACONIS LINNAEUS, 1766 (GASTEROSTEIFORMES: PEGASIDAE); A NEW RECORD TO THE DERAWAN ISLANDS, INDONESIA - Peristiwady, Teguh (Marine Research in Indonesia, 2007)
Three specimens of Eurypegasus draconis Linnaeus, 1766 were collected in seagrass beds of Samama Island, East Kalimantan, in June 2006. It was the first record of this uncommon species that widely distributes in Indian and Pacific waters. The species was characterized by 8-9 tail rings and a spine on the dorsal side of last tail ring.